Pengaruh Pendapatan Asli Daerah dan Dana Perimbangan Terhadap Pertumbuhan Ekonomi Di Provinsi Sumatera Utara - Dona Ridwan; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This study aims to find and analyze the effect of (1) Original Local Goverment Revenue, (2) General Allocation Fund, (3) Special Allocation Fund and (4) Revenue Sharing Fund on Economic Growth in North Sumatra Province by using a panel regression equation model. and using the Random Effect Model (REM) approach. The estimation results show that: (1) Original Local Government Revenue has a negative but insignificant effect on economic growth in north Sumatera Province, (2) General Allocation Fund have a positive and significant effect on economic growth in North Sumatera, (3) Special Allocation Fund have a positive effect but not significant to economic growth in North Sumatera Province, (4) Revenue Sharing Fund have a positive but insignificant effect on economic growth in Nort Sumatera Province, (5) Original Local Government Revenue, General Allocation Fund, Special Allocation Fund and Revenue Sharing Fund together have a significant effect on economic growth in North Sumatra Province. Based on the results of this study, local governments are expected to further optimize the use of Local Own Revenue and Balancing Funds, because they can have an influence on economic growth in North Sumatra Province.